Mucocele of the lower lip in a 70 y.o. patient with poorly fitted denture - a case report - Piotr Osica; Karolina Osica; Anna Janas-Naze (Kazimierz Wielki University, 2018)
The article presents a case of 70-year-old patient with mucocele of lower lip caused by poorly fitted denture.